Strategi Keberlanjutan dalam Proses Produksi Tahu: Pendekatan Lean Manufacturing untuk UMKM - Fredy Sumasto; Adhitya Nugraha Duwan Putra; Muhammad Riezqi Ibrahim; Adrian Januar Wahab; Muhammad Ryas Anugrah Sahnun; Edwin Sahrial Solih; Desy Agustin (Jurnal Serambi Engineering, 2024)
This study aims to improve the efficiency of tofu production at Haji Ripit tofu factory through the application of Lean Manufacturing principles. The analysis was conducted using the Value Stream Mapping (VSM) method to identify and overcome time waste in the production process. The results showed the main problems, namely waste waiting and waste motion. Waste waiting was identified in the process of moving the stew to the filter, while waste motion was caused by the inefficient arrangement of the filter. To overcome the waste waiting, a modification was made to the boiling furnace by adding a hole for the output of the stew. This change successfully reduced the cycle time of the pouring process from 2000 seconds to 400 seconds, with a cycle time difference of 1600 seconds. In addition, to address waste motion, a re-layout was proposed by unifying the workbenches in the molding, cutting, and packaging processes. The results of the re-layout proved the reduction of movement time from molding to cutting process from 10 seconds to none. This research makes an important contribution in the context of improving efficiency and productivity in tofu factories, and the results can serve as a reference for similar industries in improving their operational performance through the implementation of Lean Manufacturing.